Dechlorinating agent and its preparation method and application
By using spherical chlorite mesoporous composite carriers and dehydration agents of active zinc oxide components, the problems of poor performance and high cost of existing dehydration agents are solved, and efficient oil pint chlorine treatment is achieved.
Patent Information
- Application Number
- CN202111141737.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-09-28
AI Technical Summary
The existing dechlorination agents have poor performance in oil pint dechlorination treatment, especially under liquid phase reaction conditions, active components are prone to loss, and copper oxide raw materials are expensive, which limits popular application.
The spherical chlorite mesoporous composite material is used as the carrier and the active zinc oxide is supported as the dechlorination component. The dehydration agent is prepared by mixing, extrusion molding, drying and calcining.
It significantly improves the dechlorination efficiency of the oil product, reduces the chlorine content in the oil product, and has simple preparation method, easy control of conditions, and good product repeatability.
Smart Images

Figure CN115873627B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of petrochemical industry, and in particular to a dechlorinating agent and a preparation method and application thereof. Background Art
[0002] Catalytic reforming is one of the important production processes in petrochemical industry. In order to ensure the activity of the catalyst and achieve the best water-chlorine balance, water and organic chlorides need to be continuously injected. In this process, the water and HCl lost are partially accumulated in the reforming oil. The presence of a small amount of chlorine in the reforming oil will affect the quality of the top product and cause corrosion of the downstream stabilization system and extraction device. Therefore, it is very necessary to dechlorinate the reforming oil. The current mainstream propane dehydrogenation OLEFLEX process uses Pt / Al2O3 catalyst and also continuously injects organic chlorides, resulting in the accumulation of HCl in the product gas, which needs to be effectively removed by a dechlorinating agent.
[0003] The most economical solution is to use solid adsorbent to remove trace chlorides from reformate and dehydrogenation product gas. The principle of dechlorination is to fix HCl in the dechlorinator through acid-base chemical reaction. When designing a dechlorinator, the first thing to do is to choose the active component. The most studied are alkali metals, alkaline earth metals and transition metal oxides that can react with HCl. Initially, researchers prepared dechlorinators by loading transition metal oxides such as Cu and Fe on activated carbon, which pioneered the research on activated carbon-supported copper dechlorinators. At present, this type of dechlorinator has been industrialized. However, the activated carbon carrier itself has low particle strength and high surface abrasion, which can easily cause particle pulverization during use, and the metal active components are easy to lose, especially under liquid phase reaction conditions, the loss of active components is more serious, and the raw material of copper oxide itself is expensive, which limits the popularization and application of copper-based dechlorinators. Dechlorinating agents with alkali metal or alkaline earth metal oxides added to alumina as carriers show better economic performance. Related studies include impregnating 0-5% sodium oxide or potassium oxide active components on alumina carriers, doping about 10% of alkali metal components during the preparation process, or mixing multiple alkali metal components with molecular sieve components. Although dechlorinating agents have been studied to a certain extent in the prior art, the dechlorinating agents obtained are still not satisfactory in terms of dechlorination performance.
[0004] Therefore, relying on the application of new materials to develop new dechlorination agents remains an important work direction for researchers in this field. Summary of the invention
[0005] The purpose of the present invention is to overcome the defect problem of poor performance of dechlorinating agents in the prior art in the dechlorination treatment of oil products, and to provide a dechlorinating agent and a preparation method and application thereof. The dechlorinating agent is used for the dechlorination treatment of oil products and can obtain good dechlorination effect.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a dechlorinating agent, wherein the dechlorinating agent comprises a carrier and an active dechlorinating component loaded on the carrier, wherein the carrier is a spherical chlorite mesoporous composite material, the active dechlorinating component is active zinc oxide, and based on the total weight of the dechlorinating agent, the content of the carrier is 20-60% by weight, and the content of the active dechlorinating component is 40-80% by weight.
[0007] The second aspect of the present invention provides a method for preparing the aforementioned dechlorinating agent, wherein the preparation method comprises: mixing an active dechlorinating component and a spherical chlorite mesoporous composite material to obtain a mixture, then contacting the mixture with water and a pore-forming agent, stirring the mixture evenly, and then extruding, drying and calcining the mixture to obtain the dechlorinating agent.
[0008] The third aspect of the present invention provides a use of the above-mentioned dechlorinating agent in a dechlorination reaction.
[0009] Through the above technical solution, the technical solution of the present invention has the following advantages:
[0010] (1) The main components of the dechlorinating agent provided by the present invention are active zinc oxide and spherical chlorite mesoporous composite material. The dechlorinating agent contains both active dechlorinating components and mesoporous multi-level ordered pore structure, which is beneficial to the adsorption of chlorine-containing substances.
[0011] (2) The dechlorination agent provided by the present invention is used for dechlorination treatment of chlorine-containing oil products, which can effectively improve the dechlorination efficiency and significantly reduce the chlorine content in the oil products.
[0012] (3) The preparation method of the dechlorinating agent provided by the present invention is simple, the conditions are easy to control, and the product has good reproducibility.
[0013] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is the X-ray diffraction spectrum of the spherical chlorite mesoporous composite material A prepared in Example 1;
[0015] Figure 2 is a SEM scanning electron microscope image of the microscopic morphology of the spherical chlorite mesoporous composite material A prepared in Example 1;
[0016] Figure 3 3 is the pore size distribution curve of the spherical chlorite mesoporous composite material prepared in Example 1. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] A first aspect of the present invention provides a dechlorinating agent, wherein the dechlorinating agent comprises a carrier and an active dechlorinating component loaded on the carrier, wherein the carrier is a spherical chlorite mesoporous composite material, the active dechlorinating component is active zinc oxide, and based on the total weight of the dechlorinating agent, the content of the carrier is 20-60% by weight, and the content of the active dechlorinating component is 40-80% by weight.
[0019] The inventors of the present invention have found that the dechlorinating agents currently used in industry are mainly catalysts that use activated carbon as a carrier to load copper oxide. However, the activated carbon carrier itself has low particle strength and high surface wear, which can easily cause particle pulverization during use, and the metal active components are easy to lose, especially under liquid phase reaction conditions, the loss of active components is more serious; and the raw materials of copper oxide itself are relatively expensive, which limits the popularization and application of copper-based dechlorinating agents. In addition, the dechlorinating agents currently used in industry also include improved catalysts, which use aluminum oxide as a carrier, but the dechlorination performance and dechlorination efficiency are difficult to be satisfactory.
[0020] The inventors of the present invention found during the preparation research of dechlorination agent that if the dechlorination agent is prepared by using spherical chlorite mesoporous composite material as a carrier to load active dechlorination components, the dechlorination efficiency of oil products can be effectively improved.
[0021] Chlorite is a kind of OH-containing -Aluminosilicate minerals of magnesium, iron and aluminum belong to clay minerals and can be widely used in catalyst carriers, papermaking, coatings and rubber. Mesoporous molecular sieve materials have the advantages of orderly pores, adjustable pore size, large specific surface area and pore volume, so that the supported catalysts made of these mesoporous molecular sieve materials as carriers show many advantages in the preparation process of organic catalytic reactions, such as high catalytic activity, few side reactions, simple post-treatment, etc. However, the large specific surface area and high pore volume make these mesoporous molecular sieve materials have strong water and moisture absorption capabilities, which will cause these supported catalysts to agglomerate during the catalytic reaction. Therefore, if the advantages of mesoporous materials and chlorite can be combined, a new spherical composite material can be synthesized, which has both the advantages of chlorite and the advantages of mesoporous materials. In this way, the high specific surface area, large pore volume, large pore size, mesoporous molecular sieve materials with three-dimensional cubic pore structure and double pore distribution structure with hexagonal pore structure can be retained, and the agglomeration of mesoporous molecular sieve materials can be reduced and their fluidity can be increased. Adding spherical mesoporous materials containing chlorite to the dechlorinating agent can provide a skeleton structure for it, change the morphology of the active dechlorinating component, and make the active dechlorinating component evenly dispersed around it. In particular, chlorite has a special crystal interlayer structure, and metal cations can be exchanged between layers. During the preparation of the dechlorinating agent, the cation exchange of the active dechlorinating component is promoted, thereby refining the grains, improving the pore structure, and increasing the specific surface area. The water generated by the reaction of HCl gas and alkali can also enter this special interlayer structure, thereby maintaining the skeleton structure of the dechlorinating agent, thereby optimizing the chemical properties and mechanical strength of the dechlorinating agent.
[0022] According to the present invention, preferably, based on the total weight of the dechlorinating agent, when the content of the carrier is 25-55% by weight and the content of the active dechlorinating component is 45-75% by weight, the dechlorinating agent provided by the present invention is used for dechlorination treatment of oil products, and a better dechlorination effect can be obtained.
[0023] According to the present invention, more preferably, based on the total weight of the dechlorinating agent, when the content of the carrier is 30-50% by weight and the content of the active dechlorinating component is 50-70% by weight, the dechlorinating agent provided by the present invention is used for dechlorination treatment of oil products to obtain a better dechlorination effect.
[0024] According to the present invention, the dechlorination agent can be in the shape of a sphere, granules, strips, cylinders, etc.
[0025] According to the present invention, the average particle size of the spherical chlorite mesoporous composite material is 10-60 μm, and the specific surface area is 200-600 m 2 / g, the pore volume is 0.8-2.0mL / g, and the pore size is bimodal distribution; wherein the first most probable pore size and the second most probable pore size corresponding to the bimodal distribution are 3-6nm and 18-22nm, respectively.
[0026] According to the present invention, preferably, the specific surface area of the spherical chlorite mesoporous composite material is 300-400m 2 / g, the pore volume is 1.4-1.8mL / g, the pore size is bimodal, and the first most probable pore size and the second most probable pore size corresponding to the bimodal are 3.5-4.5nm and 18-21nm, respectively.
[0027] According to the present invention, in a more preferred case, the specific surface area of the spherical chlorite mesoporous composite material is 301-349m 2 / g, the pore volume is 1.5-1.7mL / g, the pore size is bimodal, and the first most probable pore size and the second most probable pore size corresponding to the bimodal are 3.6-4.2nm and 19-21nm, respectively.
[0028] According to the present invention, in the present invention, the active zinc oxide is purchased from Beijing Sinopharm Group.
[0029] According to the present invention, the preparation method of the spherical chlorite mesoporous composite material comprises:
[0030] (a) in the presence of a template and butanol, bringing tetraethyl orthosilicate into first contact with an acid agent, and subjecting the mixture obtained after the first contact to a first crystallization and a first filtration treatment to obtain a mesoporous molecular sieve material filter cake 1 having a three-dimensional cubic pore structure;
[0031] (b) subjecting ethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia to a second contact reaction, and subjecting the mixture obtained after the second contact reaction to a second crystallization and a second filtration treatment to obtain a mesoporous molecular sieve material filter cake 2 having a hexagonal pore structure;
[0032] (c) mixing the mesoporous molecular sieve material filter cake 1, the mesoporous molecular sieve material filter cake 2, silica gel and chlorite and ball-milling them, and slurrying the solid powder obtained after the ball-milling with water and spray-drying the mixture.
[0033] According to the present invention, in step (a), the molar ratio of the template, butanol and tetraethyl orthosilicate can be 1: (10-100): (10-90), preferably 1: (60-90): (50-75).
[0034] According to the present invention, the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene. Preferably, the template molecular formula is EO 20 PO 70 EO20 The template agent can be purchased commercially (for example, it can be purchased from Aldrich Company with the trade name P123).
[0035] According to the present invention, the acid agent can be any conventional substance or mixture (such as solution) that can be used to adjust the pH value. Preferably, the acid agent is hydrochloric acid. The hydrochloric acid as the acid agent is preferably used in the form of an aqueous solution. Preferably, the acid agent is hydrochloric acid with a pH value of 1-6.
[0036] According to the present invention, the butanol is preferably n-butanol.
[0037] According to the present invention, the conditions for the first contact are: temperature of 10-60°C, time of 10-72h, pH value of 1-7; in order to facilitate uniform mixing of the substances, the contact between the ethyl orthosilicate and the acid agent is preferably carried out under stirring conditions.
[0038] According to the present invention, the conditions for the first crystallization include: a temperature of 30-150° C. and a time of 10-72 hours. Preferably, the conditions for the first crystallization include: a temperature of 40-100° C. and a time of 20-40 hours. The crystallization is performed by a hydrothermal crystallization method.
[0039] According to the present invention, in step (b), the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia is 1:(0.1-1):(0.1-5), preferably 1:(0.2-0.5):(1.5-3.5).
[0040] According to the present invention, the ammonia is preferably added in the form of aqueous ammonia.
[0041] According to the present invention, the second contact reaction process of the tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia is carried out in the presence of water. Preferably, part of the water is introduced in the form of ammonia water, and part of the water is added in the form of deionized water. In the contact reaction system of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia, the molar ratio of the tetraethyl orthosilicate to water can be 1: (100-200), preferably 1: (120-180).
[0042] According to the present invention, the conditions for the second contact reaction of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia include: temperature of 25-100° C., time of 10-72 hours. Preferably, the contact reaction is carried out under stirring to facilitate uniform mixing of the substances.
[0043] According to the present invention, in step (b), the conditions for the second crystallization include: a temperature of 30-150° C. and a time of 10-72 hours. Preferably, the conditions for the second crystallization include: a temperature of 40-100° C. and a time of 20-40 hours. The crystallization is performed by a hydrothermal crystallization method.
[0044] According to the present invention, in step (c), relative to 100 parts by weight of the mesoporous molecular sieve material filter cake 1, the amount of the mesoporous molecular sieve material filter cake 2 is preferably 50-200 parts by weight; the amount of the silica gel is preferably 100-300 parts by weight; and the amount of the chlorite is preferably 40-100 parts by weight.
[0045] According to the present invention, in step (c), the ball milling can be carried out in a ball mill, the inner wall of the ball milling jar in the ball mill is preferably lined with polytetrafluoroethylene, and the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball milling jar, and for a ball milling jar of 50-150 ml, usually one grinding ball can be used; the material of the grinding balls can be agate, polytetrafluoroethylene, etc., preferably agate. The conditions of the ball milling can include: the rotation speed of the grinding balls can be 300-500r / min, the temperature in the ball milling jar can be 15-100°C, and the ball milling time can be 0.1-100h.
[0046] According to the present invention, in step (c), the solid powder is slurried with water at 25-60° C. In the slurrying process, the weight ratio of the solid powder to water can be 1:(0.1-2), preferably 1:(0.3-0.9).
[0047] According to the present invention, in step (c), the spray drying can be carried out in a conventional manner, for example, in an atomizer. The spray drying conditions may include: a temperature of 100-300°C, and a rotation speed of 10000-15000 r / min; preferably, the spray drying conditions include: a temperature of 150-250°C, and a rotation speed of 11000-13000 r / min.
[0048] According to the present invention, in step (c), the conditions for removing the template may include: a temperature of 300-600° C. and a time of 10-80 h.
[0049] According to the present invention, the first filtration and the second filtration are not specifically limited, and conventional filtration methods can be used. After the first filtration or the second filtration, washing and suction filtration are required, wherein deionized water can be used for washing, and the number of washing times is preferably 4-6 times.
[0050] The second aspect of the present invention provides a method for preparing the aforementioned dechlorinating agent, wherein the preparation method comprises: mixing an active dechlorinating component and a spherical chlorite mesoporous composite material to obtain a mixture, then contacting the mixture with water and a pore-forming agent, stirring the mixture evenly, and then extruding, drying and calcining the mixture to obtain the dechlorinating agent.
[0051] According to the present invention, the weight ratio of the active zinc oxide to the spherical chlorite mesoporous composite material is 1:(0.3-4), preferably 1:(0.8-3); more preferably 1:(1.0-2.5).
[0052] According to the present invention, the pore-forming agent is selected from one or more of sesbania powder, cellulose, polyethylene glycol, polyvinyl alcohol, starch and sodium carboxymethyl cellulose aqueous solution; preferably sodium carboxymethyl cellulose aqueous solution; the concentration of the sodium carboxymethyl cellulose aqueous solution is 0.5-10%.
[0053] According to the present invention, the drying conditions include: temperature of 70-150° C. and time of 1-16 hours.
[0054] According to the present invention, the calcination conditions include: a temperature of 250-450° C. and a time of 0.5-10 h.
[0055] The third aspect of the present invention provides a use of the above-mentioned dechlorinating agent in a dechlorination reaction.
[0056] The present invention will be described in detail below through examples.
[0057] In the following examples and comparative examples:
[0058] The pore structure parameter analysis of the molecular sieve samples and catalyst samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA. The samples were vacuum degassed at 350°C for 4 h before measurement. The specific surface area of the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.
[0059] The drying oven was manufactured by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A;
[0060] The muffle furnace is produced by CARBOLITE, model CWF1100.
[0061] Other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0062] Example 1
[0063] This example is to illustrate the preparation of the dechlorinating agent of the present invention.
[0064] (1) Preparation of spherical chlorite mesoporous composite materials
[0065] 60 g (0.01 mol) of triblock copolymer surfactant P123 was dissolved in 100 ml of hydrochloric acid aqueous solution (pH 4) and 2000 g of deionized water solution, and stirred for 4 h until P123 was dissolved to form a transparent solution. 60 g (0.8 mol) of n-butanol was added to the transparent solution and stirred for 1 h. The solution was then placed in a 40°C water bath, and 129 g (0.62 mol) of ethyl orthosilicate was slowly added dropwise to the solution. The solution was stirred for 24 h while maintaining the temperature at about 40°C and pH 4.5. The solution was then hydrothermally treated at 100°C for 24 h, filtered and washed with deionized water 4 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 1 having three-dimensional cubic pores.
[0066] Hexadecyltrimethylammonium bromide and tetraethyl orthosilicate are added to an ammonia solution with a concentration of 25 wt %, wherein the amount of tetraethyl orthosilicate added is 208 g, and the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, and ammonia to water in the ammonia solution is 1:0.4:2.5:150, and stirred at 50°C for 24 hours, and then hydrothermally treated at 80°C for 30 hours, followed by filtration and washing with deionized water for 4 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 2 with a hexagonal pore structure.
[0067] Put 10g of the prepared mesoporous molecular sieve material cake 1, 10g of the mesoporous molecular sieve material cake 2, 20g of silica gel and 7g of chlorite into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 400r / min. Close the ball mill, and mill it at a temperature of 60°C in the ball mill for 1h to obtain a solid powder; dissolve the solid powder in 50ml of deionized water, spray dry it at 200°C and a rotation speed of 12000r / min; calcine the product obtained after spray drying at 500°C in a muffle furnace for 30h to remove the template agent to obtain a spherical chlorite mesoporous composite material A.
[0068] Figure 1 The XRD spectrum of the spherical chlorite mesoporous composite material A prepared in Example 1 is shown in FIG. Figure 1 It can be seen from the small-angle spectral peaks appearing in the spherical chlorite mesoporous composite material A that the spherical chlorite mesoporous composite material A has an ordered three-dimensional cubic pore structure and a hexagonal pore structure.
[0069] Figure 2 This is a SEM scanning electron microscope image of the spherical chlorite mesoporous composite material A prepared in Example 1. Figure 2 It can be seen that the microscopic morphology of the spherical chlorite mesoporous composite material A is a mesoporous sphere with a particle diameter of 10-60 μm.
[0070] Figure 3 is the pore size distribution curve of the spherical chlorite mesoporous composite material A prepared in Example 1, from Figure 3 It can be seen that the pore size of the spherical chlorite mesoporous composite material A presents a bimodal distribution, wherein the first most probable pore size and the second most probable pore size corresponding to the bimodal distribution are 4 nm and 20 nm, respectively.
[0071] (2) Preparation of dechlorinating agent
[0072] 100g of the spherical chlorite mesoporous composite material A prepared in the above steps was uniformly mixed with 150g of active zinc oxide, and then 50g of distilled water was added for wetting, and then 70g of a 2.5% aqueous solution of sodium carboxymethyl cellulose was added. The mixture was ground into a paste, extruded, dried at 110°C for 3h, and finally calcined at 350°C for 3h to obtain a dechlorinating agent A.
[0073] Based on the total weight of the dechlorinating agent A, the content of zinc oxide is 60 weight %, and the content of the spherical chlorite mesoporous composite material is 40 weight %.
[0074] Example 2-3
[0075] This example is to illustrate the preparation of the dechlorinating agent of the present invention.
[0076] The dechlorinating agent was prepared in the same manner as in Example 1, except that the parameters in the preparation process of the spherical chlorite mesoporous composite material and the preparation process of the dechlorinating agent in Example 1 were changed, and Examples 2 and 3 were carried out to obtain spherical chlorite mesoporous composite materials B and C, and dechlorinating agents B and C, respectively.
[0077] Table 1 lists the parameters in the preparation process of the spherical chlorite mesoporous composite material and the structural parameters of the spherical chlorite mesoporous composite material.
[0078] Table 2 lists the compositions of the dechlorinating agents obtained in Examples 2-3.
[0079] Embodiment 4-7
[0080] This example is to illustrate the preparation of the dechlorinating agent of the present invention.
[0081] The dechlorinating agent was prepared in the same manner as in Example 1, except that the parameters in the preparation process of the dechlorinating agent in Example 1 were changed, and Examples 4-7 were carried out to obtain dechlorinating agent D, dechlorinating agent E, dechlorinating agent F and dechlorinating agent G, respectively.
[0082] Table 2 lists the compositions of the dechlorinating agents obtained in Examples 4-7.
[0083] Comparative Example 1
[0084] A dechlorinating agent was prepared in the same manner as in Example 1, except that step (1) was eliminated, only step (2) was retained, and 100 g of the spherical chlorite mesoporous composite material A was replaced with 100 g of commercially available alumina.
[0085] As a result, dechlorinating agent D1 was obtained.
[0086] Table 2 lists the composition of the dechlorinating agent obtained in Comparative Example 1.
[0087] Comparative Example 2
[0088] A dechlorinating agent was prepared in the same manner as in Example 1, except that step (1) was eliminated, only step (2) was retained, and 100 g of the spherical chlorite mesoporous composite material A was replaced with 100 g of commercially available chlorite.
[0089] As a result, dechlorinating agent D2 was obtained.
[0090] Table 2 lists the composition of the dechlorinating agent obtained in Comparative Example 2.
[0091] Comparative Examples 3-4
[0092] The dechlorinating agent was prepared in the same manner as in Example 1, except that the contents of the spherical chlorite mesoporous composite material and the active dechlorinating component active zinc oxide were not within the range defined in the present invention.
[0093] As a result, dechlorinating agents D3 and D4 were obtained.
[0094] Table 2 lists the composition of the dechlorinating agent obtained in Comparative Examples 3-4.
[0095] Table 1
[0096]
[0097]
[0098] Table 2
[0099] Dechlorination agent samples Active zinc oxide Spherical chlorite mesoporous composite material Dechlorinating agent A (1:0.7) 60% Spherical chlorite mesoporous composite material A, 40% Dechlorinating agent B (1:1) 50% Spherical chlorite mesoporous composite material B, 50% Dechlorinating agent C (1:0.43) 70% Spherical chlorite mesoporous composite material C, 30% Dechlorination agent D 45% 55% Dechlorinating agent E 75% 25% Dechlorination agent F 80% 20% Dechlorination agent G 40% 60% Dechlorinating agent D1 60% Commercial Alumina, 40% Dechlorinating agent D2 60% Commercial chlorite, 40% Dechlorinating agent D3 85% 15% Dechlorinating agent D4 35% 65%
[0100] Test Case
[0101] Testing of the performance of dechlorinating agents in dechlorination of chlorinated oil products
[0102] The total chlorine content of the chlorinated oil used in the test was 2508.5 mg / L.
[0103] The specific test method is as follows: 1.0g of dechlorinating agent and 50g of oil are placed in a conical flask at the same time, the conical flask is shaken in an oscillator for 3h, and the total chlorine content of the oil in the conical flask is analyzed after it is still. The reaction results are shown in Table 3.
[0104] Table 3
[0105]
[0106]
[0107] It can be seen from Table 3 that the dechlorinating agent provided by the present invention has excellent performance when used for dechlorination treatment of chlorinated oil products.
[0108] Comparing the data of dechlorination agent A and dechlorination agent D1, it can be seen that dechlorination agent A uses spherical chlorite mesoporous composite material as carrier, while dechlorination agent D1 does not contain spherical chlorite mesoporous composite material and uses commercially available ordinary alumina instead of all-silicon spherical chlorite mesoporous composite material as carrier. Compared with dechlorination agent D1, the dechlorination efficiency of dechlorination agent A is significantly improved.
[0109] Comparing the data of dechlorinating agent A and dechlorinating agent D2, it can be seen that dechlorinating agent A uses spherical chlorite mesoporous composite material as carrier, while dechlorinating agent D2 does not contain spherical chlorite mesoporous composite material, and uses commercially available ordinary chlorite instead of all-silicon spherical chlorite mesoporous composite material as carrier. Compared with dechlorinating agent D2, the dechlorination efficiency of dechlorinating agent A is significantly improved.
[0110] Comparing the data of dechlorinating agent A with those of dechlorinating agents D3 and D4, it can be seen that dechlorinating agent A uses spherical chlorite mesoporous composite material as carrier, and the contents of spherical chlorite mesoporous composite material and active dechlorination component active zinc oxide in dechlorinating agents D3 and D4 are not within the range defined by the present invention. Compared with dechlorinating agents D3 and D4, the dechlorination efficiency of dechlorinating agent A is significantly improved.
[0111] The above results indicate that the dechlorinating agent provided by the present invention has excellent performance because it contains the spherical chlorite mesoporous composite material specifically defined by the present invention.
[0112] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. Application of a dechlorinating agent in the dechlorination reaction of chlorinated oil products, characterized in that: The application includes applying a dechlorinating agent to a chlorinated oil product for dechlorination reaction, wherein the dechlorinating agent includes a carrier and an active dechlorinating component loaded on the carrier, wherein the carrier is a spherical chlorite mesoporous composite material, the active dechlorinating component is active zinc oxide, and based on the total weight of the dechlorinating agent, the content of the carrier is 20-60% by weight, and the content of the active dechlorinating component is 40-80% by weight; The spherical chlorite mesoporous composite material has an average particle size of 10-60 μm and a specific surface area of 200-600 m 2 / g, pore volume 0.8-2mL / g, pore size bimodal distribution; wherein the first most probable pore size and the second most probable pore size corresponding to the bimodal distribution are 3-6nm and 18-22nm respectively; The preparation method of the spherical chlorite mesoporous composite material comprises: (a) in the presence of a template and butanol, bringing tetraethyl orthosilicate into first contact with an acid agent, and subjecting the mixture obtained after the first contact to a first crystallization and a first filtration treatment to obtain a mesoporous molecular sieve material filter cake 1 having a three-dimensional cubic pore structure; (b) subjecting ethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia to a second contact reaction, and subjecting the mixture obtained after the second contact reaction to a second crystallization and a second filtration treatment to obtain a mesoporous molecular sieve material filter cake 2 having a hexagonal pore structure; (c) mixing the mesoporous molecular sieve material filter cake 1, the mesoporous molecular sieve material filter cake 2, silica gel and chlorite and ball-milling the mixture, and slurrying the solid powder obtained by ball-milling with water and spray-drying the mixture.
2. The use according to claim 1, wherein: Based on the total weight of the dechlorinating agent, the content of the carrier is 25-55% by weight, and the content of the active dechlorinating component is 45-75% by weight.
3. The use according to claim 2, wherein: Based on the total weight of the dechlorinating agent, the content of the carrier is 30-50% by weight, and the content of the active dechlorinating component is 50-70% by weight.
4. The use according to claim 1, wherein: In step (a), the molar ratio of the template, butanol and tetraethyl orthosilicate is 1:(10-100):(10-90).
5. The use according to claim 1, wherein: The template is polyoxyethylene-polyoxypropylene-polyoxyethylene.
6. The use according to claim 1, wherein: The acid agent is hydrochloric acid with a pH value of 1-6.
7. The use according to claim 1, wherein: In step (a), the conditions of the first contact are: temperature of 10-60° C., time of 10-72 h, and pH of 1-7.
8. The use according to claim 1, wherein: In step (a), the first crystallization conditions are: temperature of 30-150° C. and time of 10-72 h.
9. The use according to claim 1, wherein: In step (b), the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia is 1:(0.1-1):(0.1-5).
10. The use according to claim 1, wherein: In step (b), in the reaction system of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia for the second contact, the molar ratio of tetraethyl orthosilicate to water is 1:(100-200).
11. The use according to claim 1, wherein: In step (b), the second contacting conditions are: temperature of 25-100° C., and time of 10-72 h.
12. The use according to claim 1, wherein: In step (b), the second crystallization conditions are: temperature of 30-150° C. and time of 10-72 h.
13. The use according to claim 1, wherein: In step (c), relative to 100 parts by weight of the mesoporous molecular sieve material filter cake 1, the mesoporous molecular sieve material filter cake 2 is 50-200 parts by weight; the silica gel is 100-300 parts by weight; and the chlorite is 40-100 parts by weight.
14. The use according to claim 1, wherein: In step (c), during the slurrying process, the weight ratio of the solid powder to water is 1:(0.1-2).
15. The use according to any one of claims 1 to 14, wherein: The preparation method of the dechlorinating agent comprises: mixing an active dechlorinating component and a spherical chlorite mesoporous composite material to obtain a mixture, contacting the mixture with water and a pore-forming agent, stirring the mixture evenly, and then subjecting the mixture to extrusion molding, drying and calcining to obtain the dechlorinating agent.
16. The use according to claim 15, wherein: The pore-forming agent is selected from one or more of sesbania powder, cellulose, polyethylene glycol, polyvinyl alcohol, starch and carboxymethyl cellulose sodium salt aqueous solution.
17. The use according to claim 15, wherein: The preparation method of the dechlorinating agent comprises: mixing an active dechlorinating component and a spherical chlorite mesoporous composite material to obtain a mixture, contacting the mixture with water and a pore-forming agent, stirring the mixture evenly, and then subjecting the mixture to extrusion molding, drying and calcining treatment, wherein the drying conditions include: a temperature of 70-150° C. and a time of 1-16 hours.
18. The use according to claim 15, wherein: The calcination conditions include: temperature of 250-450° C. and time of 0.5-10 h.
Citation Information
Patent Citations
Zincium-calcium dechlorinating agent at normal temperature and its preparing method
CN101269294A
Chlorite mesoporous composite material, supported catalyst, preparation method thereof, application and preparation method of cyclohexanone glycerol ketal
CN105149011A
Antichlor and preparation method thereof
CN106334516A